2010
DOI: 10.1021/jp104421a
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Hydrodeoxygenation of Acrolein on a Cluster Model of MoO3

Abstract: We have explored the potential energy surface for reactions of acrolein on a Mo 3 O 9 cluster model of the MoO 3 surface to investigate the thermodynamics and kinetics of hydrogenation and selective hydrodeoxygenation. In the presence of hydrogen, conversions of acrolein to allyl alcohol, 1-propanol, and propene are all thermodynamically favorable, but the selectivity is controlled kinetically to form the least favorable product, allyl alcohol. We propose a mechanism in which coordinatively unsaturated Mo site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
74
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 89 publications
8
74
0
Order By: Relevance
“…It has been reported that Brønsted acidity directs the reaction towards acrolein-propene formation while Lewis acidity towards acetol production. 50 Taking into account the experimental results of this study, as well as relative reports, 30,43,51,52 it could be proposed that molybdenum oxide, at a reduced state, and surface hydroxyls formed due to water presence and reduction procedure, 30,53,54 acting as Brønsted acids, provide the active sites for the reaction to occur. It is of great importance that selectivity to propene increases with glycerol conversion while the overall yield to propene reaches the value of 67.6%, at 6 h of reaction time.…”
Section: Activity and Product Distribution With Timementioning
confidence: 51%
“…It has been reported that Brønsted acidity directs the reaction towards acrolein-propene formation while Lewis acidity towards acetol production. 50 Taking into account the experimental results of this study, as well as relative reports, 30,43,51,52 it could be proposed that molybdenum oxide, at a reduced state, and surface hydroxyls formed due to water presence and reduction procedure, 30,53,54 acting as Brønsted acids, provide the active sites for the reaction to occur. It is of great importance that selectivity to propene increases with glycerol conversion while the overall yield to propene reaches the value of 67.6%, at 6 h of reaction time.…”
Section: Activity and Product Distribution With Timementioning
confidence: 51%
“…Possibly, a glycerol tungstic acid ester is formed as an intermediate, which, in combination with tungsten's favorable acidic properties, leads to 13PD selectivity. [23][24][25] Interestingly, 20 to 40 % 13PD formation is observed if a tungsten containing acidic additive is used (Figure 2 c-e) in combination with a Pt based catalyst. Moreover, only very small amounts of 12PD were observed.…”
Section: Resultsmentioning
confidence: 99%
“…The intermediate species undergoes C-O cleavage and forms a final product as shown in Figure 10 (b). In the reactions of HDO, if the metaloxygen bond is too weak, it would be difficult for the catalysts to abstract oxygen from oxy-compounds, but if metal-oxygen bond is too strong, it is difficult to create surface vacancies to adsorb oxy-compound [117]. It follows the Sabatier rule that oxides with intermediate metal-oxygen bond strength are the best better supports [118].…”
Section: Sulfided W and Re Catalystsmentioning
confidence: 99%
“…Pretreatments of WO 3 and MoO 3 in H 2 produce active phases as H y WO 3-z (x is in the range of 0.9-1.3) [145] and H x MoO 3-y (x is in the range of 1.1-1.2) [117]. This new class of heterogeneous catalysts for HDO of allyl alcohol and acrolein was reported by It is interesting to investigate the activity between sulfided catalysts and corresponding reduced catalysts for HDO process.…”
Section: Reduced Metal Oxide Bronzesmentioning
confidence: 99%